Pengaruh Karir Obyektif Pada Wanita Terhadap Konflik Keluarga-Pekerjaan Kasus Pada Universitas Muhammadiyah Surakarta - Kussudyarsana, Kussudyarsana (Universitas Muhammadiyah Surakarta, 2009)
This research due to test influence of objective career at woman toward level of work family conflict. To answer research question, we investigate 51 both of woman lecturer and officer that work in university of Muhammadiyah Surakarta, and comparing different career objective. The one group was people that occupy leader in certain job and the other group was member of certain departmen. To analyze research question, we use independent t test, and regrresion analysis with dummy variable. The result suggested there are no impact of objective career toward level of conflict. All of hyphotesis testing not confirm to the empirical data.